Regional Quarantine Policy Related to Handling Covid-19 Pandemics in Various Countries - Amelia Metta Aviariska (Universitas Airlangga, 2020)
ABSTRACTBackground: Responding to the COVID-19 pandemic that has attacked Indonesia and the high rate of confirmation cases, the President established Presidential Decree No. 11 of 2020 Regarding Corona Virus Disease Public Health Determination 2019 (COVID-19) in order to reduce the number of cases COVID-19 is positive so the pandemic is over soon.Aims: The author wants to conduct a regional quarantine policy analysis that has been carried out in several countries in order to overcome the COVID-19 pandemic.Methods: The method used in writing this article is by analyzing prospective analyzes. In addition to reviewing existing policies, the authors also collected information from the media regarding regional quarantine policies in various countries to suppress and overcome the spread of COVID-19.Results: Before the policy for regional quarantine in Indonesia was implemented, many other countries had carried out regional quarantine or lockdown to reduce the COVID-19 incidence rate. China became the first country to implement a lockdown and followed by several countries such as Italy, Denmark, Spain, France, the Philippines and many others. Indonesia itself has carried out regional quarantine (PSBB) in several regions such as DKI Jakarta, West Java and East Java.Conclusion: Many countries have carried out strict regional quarantine and resulted in a decrease in the COVID-19 event curve. This encourages other countries to do the same thing so that the COVID-19 pandemic can soon be overcome so that the people's economy can be stable again ABSTRAK Latar belakang: Menyikapi adanya pandemic COVID-19 yang telah menyerang Indonesia dan juga tingginya angka kenaikan kasus konfirmasi, Presiden menetapkan Keputusan Presiden Republik Indonesia Nomor 11 Tahun 2020 Tentang Penetapan Kedaruratan Kesehatan Masyarakat Corona Virus Disease 2019 (COVID-19) tujuan untuk menekan angka kasus COVID-19 yang positif sehingga pandemic segera berakhir.Tujuan: Penulis ingin melakukan analisis kebijakan karantina wilayah yang telah dilakukan di beberapa negara dalam rangka mengatasi pandemic COVID-19.Metode: Metode yang digunakan dalam penulisan artikel ini dengan melakukan telaah dengan analisis yang bersifat prospektif. Selain melakukan telaah kebijakan yang ada, penulis juga mengumpulkan informasi yang berasal dari media terkait kebijakan karantina wilayah di berbagai negara untuk menekan dan mengatasi penyebaran COVID-19.Hasil: Sebelum diterapkan kebijakan untuk karantina wilayah di Indonesia, telah banyak negara-negara lain yang melakukan karantina wilayah atau lockdown guna menekan angka kejadian COVID-19 terus meningkat. China menjadi negara pertama yang menerapkan lockdown dan diikuti beberapa negara seperti Italia, Denmark, Spanyol, Perancis, Filipina dan masih banyak lainnya. Indonesia sendiri telah melakukan karantina wilayah (PSBB) dibebeapa wilayah seperti DKI Jakarta, Jawa Barat dan Jawa Timur.Kesimpulan: Telah banyak negara yang melakukan karantina wilayah secara ketat dan meghasilkan penurunan kurva angka kejadian COVID-19. Hal ini mendorong negara lain untuk melakukan hal yang sama agar pandemic COVID-19 ini segera dapat diatasi sehingga perekonomian masyarakat dapat stabil Kembali.